2001
DOI: 10.1046/j.1440-1819.2001.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Associative processing and paranormal belief

Abstract: In the present study we introduce a novel task for the quantitative assessment of both originality and speed of individual associations. This 'BAG' (Bridge-the-Associative-Gap) task was used to investigate the relationships between creativity and paranormal belief. Twelve strong 'believers' and 12 strong 'skeptics' in paranormal phenomena were selected from a large student population (n > 350). Subjects were asked to produce single-word associations to word pairs. In 40 trials the two stimulus words were seman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 45 publications
(71 reference statements)
2
73
0
1
Order By: Relevance
“…Indeed, high MI might also predict a later mood disorder (Chapman et al, 1994) and is a common feature not only of the schizophrenia spectrum disorders but also a symptom of some personality disorders (eg Lyons et al, 1995;Kwapil et al, 1997). Thus, positive schizotypy may be accompanied by a relative hyperdopaminergia, but yet reflects just one of the many DA-mediated variations of the human mind and personality (Horrobin, 1998;Previc, 1999) accompanied by distinct cognitive capacities (Gianotti et al, 2001;Weinstein and Graves, 2002) and, ultimately, an unusual way of perceiving the world (Wolfradt et al, 1999;Sto + ckenius and Brugger, 2000;McCreery and Claridge, 2002;Van de Ven and Merckelbach, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high MI might also predict a later mood disorder (Chapman et al, 1994) and is a common feature not only of the schizophrenia spectrum disorders but also a symptom of some personality disorders (eg Lyons et al, 1995;Kwapil et al, 1997). Thus, positive schizotypy may be accompanied by a relative hyperdopaminergia, but yet reflects just one of the many DA-mediated variations of the human mind and personality (Horrobin, 1998;Previc, 1999) accompanied by distinct cognitive capacities (Gianotti et al, 2001;Weinstein and Graves, 2002) and, ultimately, an unusual way of perceiving the world (Wolfradt et al, 1999;Sto + ckenius and Brugger, 2000;McCreery and Claridge, 2002;Van de Ven and Merckelbach, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when presented with images composed of visual noise, Blackmore and Moore (1994) found that psychic believers were significantly more likely to see patterns in the noise than skeptics (see also Riekki et al, 2013;van Elk, 2013). Similarly, using a word association task, Gianotti et al (2001) found that believers in a variety of paranormal phenomena produced more idiosyncratic words or more distant associations than did skeptics. It also has been suggested that some kinds of paranormal beliefs -and particularly paranormal experiences -might be related to abnormal neurocognitive development or schizotypy (see Brugger & Graves, 1997).…”
Section: Implications and Future Directionsmentioning
confidence: 95%
“…Eysenck and Furnham, 1993;Gianotti et al, 2001;Kline and Cooper, 1986;Merten and Fischer, 1999;O'Reilly et al, 2001;Poreh et al, 1994;Rawlings and Toogood, 1997;Rushton, 1990;Rust et al, 1989;Graves, 2001, 2002;Woody and Claridge, 1977;Zanes et al, 1998) but currently, there is little support for enhanced creative ability in schizophrenics (Andreasen and Powers, 1975;Cropley and Sikand, 1973;Keefe and Magaro, 1980;Shimkunas and Murray, 1974). Yet, several studies using retrospective analyses of birth records, found support for increased creativity in the relatives of schizophrenic individuals, rather than in the probands themselves (Karlsson, 1970(Karlsson, , 1984.…”
Section: Introductionmentioning
confidence: 99%